Unusual severe fungal pneumonia in Vietnamese potbelly pigs: two cases. Issue 3 (24th August 2020) - Heller, Meera; Busch, Roselle; Koehne, Amanda; Keating, M Kelly; Mohr, Charles
SUMMARY: Two 18‐month‐old, castrated male Vientamese potbelly pigs presented for diagnosis and treatment of respiratory disease of two to three weeks duration which had been non‐responsive to antibiotic therapy. The pigs were unrelated, from separate households and presented roughly a year apart. Both pigs presented in the summer months, and were from the mid‐central valley of California. Diagnostics included complete blood count, serum biochemistry, thoracic radiographs, thoracic ultrasound examination and ultrasound‐guided thoracocentesis. Findings included severe pleural effusion and large thoracic masses in both cases. Thoracocentesis revealed suppurative exudate in one case and mixed inflammatory exudate in the second; both cases were negative on bacterial culture. Treatment in each case was limited as the severity of the disease lead to euthanasia of the patients. Definitive diagnosis of granulomatous fungal pneumonia was obtained on postmortem examination of both patients.